Evaluation of Cathode Gas Composition and Temperature Influences on Alkaline Anion Exchange Membrane Fuel Cell (AAEMFC) Performance - Leyla, Topal; Nunes Kirchner, Carolina; Germer, Wiebke; Zobel, Marco; Dyck, Alexander (Center of Biomass & Renewable Energy, Diponegoro University, 2014)
The effects of different temperatures (55, 65, 75 and 85 °C) and cathode gas compositions (O2, synthetic air, air and 90% synthetic air+10% CO2) on alkaline anion exchange membrane fuel cell (AAEMFC) were evaluated. Membrane electrode assemblies (MEA) were fabricated using commercial anion exchange membrane (AEM) in OH- form and Pt catalyst. Polarization curves and voltage responses during constant current were performed in order to describe the influences of temperature and gas composition on the AAEMFC performance. The experimental results showed that the fuel cell performance increases with elevating temperatures for all applied gas compositions. Highest power density of 34.7 mW cm-2 was achieved for pure O2 as cathode feed. A decrease to 20.3 mW cm-2 was observed when cathode gas composition was changed to synthetic air due to reduction of the O2 partial pressure. The presence of CO2 in atmospheric air applied to the cathode stream caused a further drop of the maximum power density to 15.2 mW cm-2 driven by neutralization of OH- ions with CO2.